Pengaruh Kualitas Produk Dan Harga Jual Terhadap Loyalitas Konsumen Dengan Kepuasan Konsumen Sebagai Variabel Intervening Pada Industri Bakso Kembar Kota Metro - Ratmono; Selamet Fuadi; Riana Prameswari (Jurnal Manajemen DIVERSIFIKASI, 2024)
This study aimed to determine the direct effect of product quality and selling price on consumer loyalty with consumer satisfaction as an intervening variable. This research was a quantitative research by measuring product quality variables. Selling price, loyalty, and satisfaction were by using a closed questionnaire. The questionnaire scoring scale for each variable was 1-5 so theoretically the range of scores obtained by respondents was between 20-100. Data collection was carried out by distributing questionnaires to a sample of 50 respondents. Data analysis in this study used path analysis (Path) with the help of the SPSS Version 20.0 application. The results showed that there was a direct influence between product quality and customer satisfaction in the Metro City Bakso Kembar Home Industry. There is a direct influence of the selling price on the satisfaction of the Metro City Bakso Kembar Home Industry. There is a direct effect of product quality on the loyalty of the Metro City Bakso Kembar Home Industry. There is a direct influence of the selling price on consumer loyalty of the Metro City Bakso Kembar Home Industry. There is a direct influence between consumer satisfaction and consumer loyalty in the Metro City Bakso Kembar Home Industry.